Mitochondrial Sirtuin-3 (SIRT3) Prevents Doxorubicin-Induced Dilated Cardiomyopathy by Modulating Protein Acetylation and Oxidative Stress. (14th April 2022) - Tomczyk, Mateusz M.; Cheung, Kyle G.; Xiang, Bo; Tamanna, Nahid; Fonseca Teixeira, Ana L.; Agarwal, Prasoon; Kereliuk, Stephanie M.; Spicer, Victor; Lin, Ligen; Treberg, Jason; Tong, Qiang; Dolinsky, Vernon W.
Abstract : Background: High doses of doxorubicin put cancer patients at risk for developing dilated cardiomyopathy. Previously, we showed that doxorubicin treatment decreases SIRT3 (sirtuin 3), the main mitochondrial deacetylase and increases protein acetylation in rat cardiomyocytes. Here, we hypothesize that SIRT3 expression can attenuate doxorubicin induced dilated cardiomyopathy in vivo by preventing the acetylation of mitochondrial proteins. Methods: Nontransgenic, M3-SIRT3 (truncated SIRT3; short isoform), and M1-SIRT3 (full-length SIRT3; mitochondrial localized) transgenic mice were treated with doxorubicin for 4 weeks (8 mg/kg body weight per week). Echocardiography was performed to assess cardiac structure and function and validated by immunohistochemistry and immunofluorescence (n=4–10). Mass spectrometry was performed on cardiac mitochondrial peptides in saline (n=6) and doxorubicin (n=5) treated hearts. Validation was performed in doxorubicin treated primary rat and human induced stem cell derived cardiomyocytes transduced with adenoviruses for M3-SIRT3 and M1-SIRT3 and deacetylase deficient mutants (n=4–10). Results: Echocardiography revealed that M3-SIRT3 transgenic mice were partially resistant to doxorubicin induced changes to cardiac structure and function whereas M1-SIRT3 expression prevented cardiac remodeling and dysfunction. In doxorubicin hearts, 37 unique acetylation sites on mitochondrial proteins were altered. Pathway analysis revealed these proteins are involved in energy production, fatty acid metabolism, and oxidative stress resistance. Increased M1-SIRT3 expression in primary rat and human cardiomyocytes attenuated doxorubicin-induced superoxide formation, whereas deacetylase deficient mutants were unable to prevent oxidative stress. Conclusions: Doxorubicin reduced SIRT3 expression and markedly affected the cardiac mitochondrial acetylome. Increased M1-SIRT3 expression in vivo prevented doxorubicin-induced cardiac dysfunction, suggesting that SIRT3 could be a potential therapeutic target for mitigating doxorubicin-induced dilated cardiomyopathy.